To the organic production development in Ukraine - Kustovska, O.; Smoliye, Y. (Land Management, Cadastre and Land Monitoring, 2019)
The article analyzes the development of organic production in Ukraine. It has been established that organic production in our country has recently expanded considerably due to the need to provide natural food products to the population, as well as the reproduction of natural fertility of soils and biodiversity of the environment with the implementation of a careful attitude towards nature, producer and consumer. The results of the Kyiv population survey, the attitude of people to organic products and goods, their impact on human health and on the state of the environment, as well as the formation of the value of such products, have been analyzed. The factors influencing the formation of value and the development of the market of organic products in Ukraine are substantiated, in particular, the main ones are considerable expenses in production and processing, as well as the passage of the corresponding certification. Adoption of the Law of Ukraine "On Basic Principles and Requirements for Organic Production, Circulation and Marking of Organic Products" is important for harmonization of national legislation with European regulation in the field of organic production and circulation of products. It establishes the general principles of legal regulation in the field of organic production, circulation and labeling of organic products, which should give an additional impetus to the sustainable development of organic production in Ukraine. It is also proved that the demand for organic products increases with the increase of the country’s economic development, welfare, education and general awareness of the population. Key words: organic production development, consumers of organic products, organic land, organic, labeling and circulation of organic products.